Eight o'clock tales - Blyton, Enid (Mammoth London, 1993)
A collection of adventures in which a brave scarecrow saves Princess Peronel from kidnap; two naughty children eat some magic shrinking sweets, and Mollie pays a visit to a very special woman who makes her doll come to life.